Teacher Communication Strategies in Dealing with Differences in Character and Emotions of Elementary School Students - ENDRO SUGIONO; Dian Susetyo; Happy Maria Yunita Sari (Universitas PGRI Semarang, 2026)
Differences in students’ character and emotional conditions are an inherent aspect of the learning process in elementary schools. Teachers are therefore required to possess effective communication strategies to manage this diversity constructively. This study aims to explore and describe teachers’ communication strategies for addressing differences in character and emotions among elementary school students. This research employed a qualitative case study design. Data were collected through in-depth interviews, classroom observations, and documentation involving elementary school teachers selected using purposive sampling. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that teachers use empathetic communication, adapt their communication styles to students’ character traits, employ both verbal and nonverbal communication, and apply persuasive and reflective approaches to manage students’ emotions and behaviors. These communication strategies contribute to creating a conducive classroom climate, enhancing student engagement, and supporting students’ social-emotional development. This study emphasizes that teacher communication plays a strategic role not only in delivering instructional content but also in fostering a psychologically safe and supportive learning environment. The findings are expected to serve as a reference for developing elementary school teachers’ communication competencies and for educational policies that promote a humanistic approach to learning